Evaluation of alternatives for the evolution of palm oil mills into biorefineries. (December 2016) - Garcia-Nunez, Jesus Alberto; Rodriguez, Deisy Tatiana; Fontanilla, Carlos Andrés; Ramirez, Nidia Elizabeth; Silva Lora, Electo Eduardo; Frear, Craig Stuart; Stockle, Claudio; Amonette, James; Garcia-Perez, Manuel
Abstract: Six alternatives for the conversion of an average Colombian palm oil mill (30 t h −1 of fresh fruit bunches (FFB) into biorefineries were evaluated. The alternatives studied were: (C1) Production of biogas from the Palm Oil Mill Effluents (POME), (C2) Composting of empty fruit bunches (EFB) and fiber, (C3) Biomass combustion for high pressure steam combined heat and power, (C4) Pellets production, (C5) Biochar production and, (C6) Biochar and bio-oil production. The available biomass could result in up to 125 kWh of electricity, 207 kg of compost, 125 kg of pellet, 44 kg of biochar and 63 kg of bio-oil per metric ton of FFB. The global warming potential (GWP), eutrophication potential (EP), net energy ratio (NER), capital expenditures (CAPEX), operational costs (OPEX), net present value (NPV) and internal rate of return (IRR) were calculated for all the alternatives. GHG reductions of more than 33% could be achieved. Anaerobic digestion and composting contributed to 30% reduction of the EP. The CAPEX for all of the biorefinery alternatives studied varies between 0.7 $ t −1 and 2.8 $ t −1 of FFB. The OPEX varies between 1.6 $ t −1 and 7.3 $ t −1 of FFB. The NPV for viable scenarios ranged between 2.5 million and 13.9 million US dollars. The IRR calculated varied between 3% and 56% and the payback periods were between 3 and 8 years. The total extra incomes reached values up to 15.2 $ t −1 of FFB. Overall the pellets production biorefinery was the preferred alternative. Highlights: Six biorefinery concepts were compared using a systematic methodology. Technical, economic and environmental indicators were used in a decision matrix. Biogas from POME and pellets production from solid residues have the best economic performance. The production of biochar and heat is the option with the best environmental performance. Compared with the baseline case, reductions of GHG emissions from 33 to 100% are achievable.